NEUROPATI PERIFER PADA PENYANDANG TALASEMIA DI POLIKLINIK HEMATOONKOLOGI RSUP DR HASAN SADIKIN BANDUNG - Uni Gamayani,* Fanny Adhy Putri,* Nushrotul Lailiyya,* Pandji Irani Fianza,** Ramdan Panigoro*** (Neurona Majalah Kedokteran Neuro Sains, 2019)
INTRODUCTION THALASSEMIA IS AN INHERITED BLOOD DISORDER WITH HIGH PREVALENCE THAT CAN LEAD TO VARIOUS NEUROLOGICAL COMPLICATIONS SUCH AS PERIPHERAL NEUROPATHY PERIPHERAL NEUROPATHY IN THALASSEMIA PATIENTS IS COMMONLY SUBCLINICAL CHRONIC HYPOXIA DUE TO ANEMIA AND IRON DEPOSITION ARE THOUGHT TO BE THE RISK FACTORS FOR NEUROPATHY IN THALASSEMIA NERVE CONDUCTION STUDY NCS IS THE GOLD STANDARD IN DIAGNOSING PERIPHERAL NEUROPATHY